Working with Excel refreshing math skills for management - Chaffe-Stengel, Priscilla M.; Stengel, Donald N. ([New York, N.Y.] (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2012)
Managers and analysts routinely collect and examine key performance measures to better understand their operations and make good decisions. Being able to render the complexity of operations data into a coherent account of significant events requires an understanding of how to work well in the electronic environment with raw data. Although some statistical and financial techniques for analyzing data are sophisticated and require specialized expertise, there are methods that are understandable by and applicable to anyone with basic algebra skills and the support of a spreadsheet package. While specialized software packages may be used in a particular business setting, Microsoft Excel is routinely available on computer desktops. Managers who have been in the field any length of time may not be sufficiently familiar with the capabilities of Excel to make optimal use of its functionalities. Prior to undertaking a program to pursue executive training, managers who are refreshed with basic algebra skills and the capabilities of Excel will be prepared to develop a richer understanding from their more advanced work.
Preface -- 1. Working with numbers and equations -- 2. Working with automated functions in Excel -- 3. Working with data -- 4. Working with mathematical models -- 5. Working with personal planning over time -- Notes -- Index.
Part of: 2012 digital library.
Includes bibliographical references and index.
Also available in print.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Keywords: Microsoft Excel (Computer file); Business mathematics -- Computer programs; Microsoft Excel; refreshing math skills; business math; statistical analysis; financial analysis; mathematical modeling; Electronic books